The Necessary Parameters Calculation for CSMC Mechanical Analysis - Wang, Xianewei; Wang, Zhaoliang; He, Qing; Li, Xiulian (Manufacturing Technology Journal, 2019)
The Central Solenoid Model Coil is a hybrid superconducting coil being developed in Institute of Plasma Physics Chinese Academy of Sciences. The R&D of Central Solenoid Model Coil will lay the foundation for the fabrication of China Fusion Engineering Test Reactor Central Solenoid coil. One of the main purposes during the R&D of Central Solenoid Model Coil is to verify its mechanical performance under the complicated load cases. In order to efficiently and accurately carry out the mechanical analysis, some necessary parameters such as the electromagnetic state under assembly error, the thermal contact resistance and the equivalent material property of conductor winding packet should be calculated in advance. The electromagnetic state here mainly refers to the asymmetric magnetic field and electromagnetic force. The calculation of magnetic density is based on elliptical integrals, the results will provide guidance for the assembly optimization of coil modules. And the subsequently obtained electromagnetic force will offer load boundary condition for the coil stability analysis. The thermal contact resistance is calculated under the assumption that the interface asperity approximately obeys the Gaussian distribution. The thermal contact resistance will be used in the thermal analysis. And the key advantage is which makes the prediction of preload force variation more accurate during coil the cooling down process. The equivalent material property is calculated by using generalized Hook's law and finite element method. Based on the equivalent material property, the coupling analysis model of CSMC will be significantly simplified. Moreover, it makes CSMC full model analysis under non-uniform loads become possible.
Keywords: CSMC; assembly error; magnetic density; equivalent material property; TCR